A Trans-Scale Young' Modulus Calculation Model of ITZ Based on Void Shape Randomness and Calcium Hydroxide Enrichment. (26th August 2020) - Liu, Junqing; Zuo, Fan; Liu, Chao
Abstract : The randomness of void shape and enrichment of calcium hydroxide are significant in interfacial transition zone (ITZ) of concrete; however, current theoretical models of ITZ do not include these features. In this article, ITZ was regarded as a three-phase composite material, and the pore morphological parameters were defined according to the characteristics of microscopic pores, and the corresponding random distribution function was constructed. The calcium hydroxide enrichment factor was introduced, and a cross-scale ITZ Young's modulus calculation model was established in combination with the Mori–Tanaka method. The reliability of the proposed model in this paper was verified through comparison to experimental results in a reference.